Backbone structure of front vehicle. - Sahari, Barkawi (2005)

(untitled)
A method to enhance the structural integrity on front floor natural gas vehicle (NGV) panel on vehicle such that it is crash resistant is provided, by the way of a reinforcement backbone component which is preferably in the form of ribs integrated to the backbone reinforcement by such means as sheet presswork or other similar methods.